Acrokeratoelastoidosis With Severe Anaemia - Sarkar Rashmi; Thami Gurvinder P; Kanwar Amrinder J (Wolters Kluwer Medknow Publications, 2000)
Acrokeratoelastoidosis is an uncommon marginal keratoderma of sporadic or familial origin. We report here an interesting case of the severe from of acrokeratoelastoidosis in an elderly patient associated with severe anemia and acroosteolysis.